IQ and governance contribute to entrepreneurship, but in different ways - Suhaimi, Siti Shazwani; Burhan, Nik Ahmad Sufian; Sabri, Mohamad Fazli; Abdul Rahman, Abdul Razak; Ibrahim, Saifuzzaman (Council for Social and Economic Studies, 2020)
Previous studies have revealed that national average intelligence (IQ) is a strong indicator of national entrepreneurial potential. This study examined the role of governance quality in regulating the effect of IQ on entrepreneurial activity measured as new business entry density. Employing robust regression analysis, IQ was found to be nonsignificant on entrepreneurial activity, while the effect of governance was found to be both positive and significant. However, there was strong evidence of the negative interaction between IQ and governance, which suggests that good governance raises entrepreneurial activity more in low-IQ than in high-IQ countries. Additional regressions were also carried out employing the ease of doing business (EDB) index as a measure of entrepreneurship. Here, the results demonstrated that IQ, and not governance was highly significant on the EDB. Moreover, the interaction between IQ and governance was non-significant, which implies that the governance quality did not regulate the effect of IQ on the EDB. This study concluded that national average IQ is effective at providing nations with an excellent regulatory environment for entrepreneurship. However, it requires good governance, and not IQ, in order to build people's confidence before they start new entrepreneurial ventures given it involves risks and uncertainty.